Agritourism farms as places of providing therapeutic services for people with autism spectrum disorder - Roman, Michał; Kawęcki, Norbert; Kudinova, Iryna; Niedziółka, Arkadiusz; Szczucka, Ewa; Wojcieszak-Zbierska, Monika (Turystyka i Rozwój Regionalny, 2024)
The aim of the article was to present the development of agritourism farms in terms of providing therapeutic services for people with autism. The literature review concerned Polish and Ukrainian farms. Autism in children can also be treated through contact between patients and domestic and farm animals. Therapies involving animals are called zootherapy and can be carried out in care farms, and additionally in those where tourist recreation is possible i.e. agritourism farms. The article draws attention to the benefits of contact between children with autism spectrum disorders and animals. The study presents a case study from Poland.